2009
DOI: 10.1002/j.0022-0337.2009.73.5.tb04736.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Postgraduate Dental Students’ Performance in a Biostatistics and Research Design Course

Abstract: Comprehension of biostatistics and principles of research design is important for literature evaluation and evidencebased practice in dentistry as well as for researchers wishing to have their publications accepted by international journals. This study investigated the contribution of several factors to postgraduate dental student performance in a biostatistics and research design course. All of the subjects in this study were dental school graduates currently enrolled in postgraduate programs leading to maste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 28 publications
3
46
2
Order By: Relevance
“…The result was similar to those of the study by Zamani and Kaboodi (2017) on Iranian students, and Siddiqi et al (2012) and Haq et al (2012) in Pakistan. 3 But in studies by Moshabab (2016) and Al-Saud (2013) in Saudi Arabia, Murphy et al (2004) in the USA, and Tantawi (2009) in Egypt, the predominant learning style of most dental students was multimodal, 6,[20][21][22] which is not in line with the result of the current study. The reasons for inconsistency between the results of the current study and the aforementioned studies may be differences in personal characteristics of the studied subjects and the teaching method of lecturers in the colleges.…”
Section: Discussioncontrasting
confidence: 84%
“…The result was similar to those of the study by Zamani and Kaboodi (2017) on Iranian students, and Siddiqi et al (2012) and Haq et al (2012) in Pakistan. 3 But in studies by Moshabab (2016) and Al-Saud (2013) in Saudi Arabia, Murphy et al (2004) in the USA, and Tantawi (2009) in Egypt, the predominant learning style of most dental students was multimodal, 6,[20][21][22] which is not in line with the result of the current study. The reasons for inconsistency between the results of the current study and the aforementioned studies may be differences in personal characteristics of the studied subjects and the teaching method of lecturers in the colleges.…”
Section: Discussioncontrasting
confidence: 84%
“…Academic performance, regardless of type of examination (lecture or laboratory) was similar among students grouped by learning styles in this study, and was not influenced by the amount of time of materials were available. Academic performance has been shown by some to be significantly better for students whose learning style matches the dominant course component (El Tantawi, ; Dobson, ; Koch et al, ). The kinesthetic learning preference has been positively associated with academic success in courses where the bulk of the students' time is spent in kinesthetic activities (Koch et al, ) and negatively associated with performance when kinesthetic activities are de‐emphasized (Good et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Students' academic progression, or possibly assessment techniques, might also explain the differences between findings in the aforementioned studies and these data. The significant associations between VARK learning styles and academic performance have been reported primarily among cohorts of professional students such as nursing and dentistry (Alkhasawneh et al, ; El Tantawi, ; Koch et al, ) who are engaged in higher level coursework. Indeed, relationships between VARK learning styles and performance were found only among advanced students enrolled in higher level courses, but not among those enrolled in general biology courses (Good, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They advise that teachers should recognize that their dental students have different learning styles, reflect on their teaching methods and then contemplate incorporating other preferences [13]. A study to determine the factors that affected post-graduate dental students" performance in a Biostatistics course concluded that teachers of dental students should match the learning preferences of as many of their students as possible by using multiple ways of presentation instead of restricting themselves to using only a single method [14]. Felder cautions that while there is no point in tailoring teaching to each student, a teacher who assumes that a "single one-size-fits-all approach" will satisfy the requirements of every student is also wrong [2].…”
Section: Introductionmentioning
confidence: 99%